Subregion specific monoaminergic signaling in the female rat striatum during nicotine abstinence - Erika Lucente; Davide Cadeddu; Christian E Edvardsson; Mia Ericson; Elisabet Jerlhag; Louise Adermark (Addiction Neuroscience)
Women report more negative effect during nicotine abstinence, a state that may increase the risk of relapse. As monoamines play a key role in mood regulation the aim of this study was to outline changes in monoaminergic signaling during nicotine abstinence. To this end, tissue levels of dopamine and serotonin, as well as the impact displayed by the dopamine D2 receptor agonist quinpirole or 5-HT on excitatory neurotransmission was assessed in female rats subjected to three weeks of nicotine exposure followed by abstinence. Studies were conducted in the nucleus accumbens (nAc), a structure associated with the acute rewarding properties of nicotine, and the dorsolateral striatum (DLS), a region linked to the formation of habits. Data demonstrate that the monoaminergic profile is subregions specific, with higher levels of dopamine in the DLS, but higher levels of serotonin in the nAc. The influence displayed by quinpirole or 5-HT on excitatory neurotransmission was, however, subregion-independent. Repeated exposure to nicotine produced a robust and long-lasting behavioral sensitization to the locomotor stimulatory properties of nicotine, with no sustained changes in monoaminergic profiles when assessed in striatal tissue after five days of abstinence. However, ex vivo electrophysiological recordings demonstrated a subregion specific change in the responsiveness to bath perfused 5-HT, with a blunted response in the DLS, and enhanced synaptic depression in the nAc. In conclusion, while nicotine abstinence was not associated with sustained changes in tissue monoamine levels, repeated nicotine exposure produced subregion-specific neuroplasticity which might contribute to the high risk of nicotine relapse.